Participatory Readership: Reconstructing the Historical Subscribership of South Today - Butchart, Megan (Papers of the Bibliographical Society of Canada / Cahiers de la Société bibliographique du Canada, 2024)
Despite the emerging proliferation of periodical studies scholarship attentive to various facets of the publishing circuit, relatively little is known about the readers of historical periodicals. Who were they? How were they reading? Why were they reading? How did readers participate in the work of periodicals discursively and non-discursively? This article outlines the process of reconstructing, from archival subscription records, the historical subscribership of South Today, a “little” literary magazine and activist publication published in the American South in the 1930s and 1940s by editors Lillian Smith and Paula Snelling. Combining the findings of this data with reader testimony in the magazine and archive, I consider the difference between “imagined” and “real” readerships and investigate how Smith and Snelling’s curation of readerly community spaces—and the resultant reader participation both on and off the page—contributed to the magazine’s development and community-based political activism. Although South Today has fallen somewhat into obscurity, it had a relatively large circulation and long run for a little magazine, and it serves as an insightful publication in the history of the long civil rights movement. Furthermore, its community approach to publishing and openly anti-segregationist politics make it an interesting candidate for a study of readership, for as South Today was increasingly subjected to state surveillance, reading the magazine became more and more of a political act. This article contributes not only to studies of little magazines and their readerships generally, but also proposes that understanding South Today’s politics and historical significance necessitates a study of its approach to readership. Ultimately, this article offers evidence of South Today’s readers as active participants rather than passive consumers, and argues that these peripheries around print objects are important sites of community and activism that deserve greater attention.